CYP1B1 and MYOC Mutations in Vietnamese Primary Congenital Glaucoma Patients. Issue 5 (May 2016) - Do, Tan; Shei, William; Chau, Pham Thi Minh; Trang, Doan Le; Yong, Victor H.K.; Ng, Xiao Yu; Chen, Yue Ming; Aung, Tin; Vithana, Eranga N.
Abstract : Purpose: Primary congenital glaucoma (PCG, OMIM 231300), the most common glaucoma in infancy, is caused by developmental defects in the anterior chamber angle. The 3 implicated genes are cytochrome P450 family I subfamily B polypeptide 1 ( CYP1B1 ), latent transforming growth factor β-binding protein 2 ( LTBP2 ), and myocilin ( MYOC ). In this study, we sought to determine CYP1B1 and MYOC sequence variations in a Vietnamese cohort of index cases with PCG and their families. Methods: Thirty Vietnamese subjects with PCG and 120 normal Vietnamese subjects were recruited. PCG was defined by the presence of at least 2 of the following clinical manifestations: increased corneal diameter (>10 mm at birth), corneal edema, Haab's striae, optic disc changes, and absence of other ocular or systemic diseases associated with childhood glaucoma. The coding exons, intron and exon boundaries, and untranslated regions of CYP1B1 and MYOC genes were PCR amplified and subjected to bidirectional sequencing in all subjects. Results: We identified 2 homozygous and 3 heterozygous CYP1B1 sequence alterations in our study subjects. Among the 5 mutations identified, 2 (p.H279L and p.L283F) were novel mutations, whereas 3 (p.A121_S122insDRPAFA, p.L107V, and p.V320L) had been previously reported in PCG cases. None of these mutations was observed in any of the 120 controls. Haplotypes generated with 6 non–disease-causing intragenic single nucleotide polymorphisms detected in CYP1B1 indicated that the most common haplotype in Vietnamese population is similar to that found in Chinese and Japanese. The genotype-phenotype correlation showed no significant difference between mutation and no-mutation groups for quantitative clinical features (presenting intraocular pressure, corneal diameter, number of surgeries performed, the cup-to-disc ratio) as well as for qualitative factors (bilateral cases, phenotype severity, and the prognosis) ( P >0.05). Conclusions: Five out of 30 families with PCG (16.7%) had disease attributable to CYP1B1 alterations suggesting that CYP1B1 is not the major gene causing PCG in Vietnamese unlike in the case of Arab or Romany patients. This percentage is similar to that detected in studies of Japanese and Chinese patients with sporadic PCG. PCG has proven to be an ocular disease of genetic heterogeneity, calling for further studies to identify novel genes causing this disease. Abstract : Supplemental Digital Content is available in the text.